Clopidogrel pretreatment in primary percutaneous coronary intervention: Prevalence of high on-treatment platelet reactivity and impact on preprocedural patency of the infarct-related artery - Ferreiro, José Luis; Homs, Sílvia; Berdejo, Javier; Roura, Gerard; Gómez-Lara, Josep; Romaguera, Rafael; Teruel, Luis; Sánchez-Elvira, Guillermo; Marcano, Ana Lucrecia; Gómez-Hospital, Joan Antoni; Angiolillo, Dominick J.; Cequier, Ángel (Thrombosis and Haemostasis, 2013)
To date, there is limited data on levels of platelet inhibition achieved in patients with ST-elevation myocardial infarction (STEMI) who are loaded with clopidogrel and aspirin (ASA) prior to undergoing primary percutaneous coronary intervention (P-PCI). The aim of this investigation was to evaluate the percentage of STEMI patients with high on-treatment platelet reactivity (HPR) to clopidogrel at the time of initiating P-PCI and its association with the initial patency of the infarct-related artery (IRA). This prospective pharmacodynamic study included 50 STEMI patients, previously naïve to oral antiplatelet agents, who received 500-mg ASA and 600-mg clopidogrel loading doses prior to P-PCI. Platelet function assessment was performed at the beginning of the procedure using various assays, including VerifyNow™ system (primary endpoint), light transmission aggregometry and multiple electrode aggregometry. The percentage of patients with suboptimal response to clopidogrel and ASA assessed with the VerifyNow™ system was 88.0% and 28.6%, respectively. Similar results were obtained with the other assays used. A higher percentage of patients with initial patency of the IRA was observed among those patients without HPR compared with those with HPR to clopidogrel (66.7% vs 15.9%; p=0.013), while no differences were observed regarding postprocedural angiographic or electrocardiographic outcomes. In conclusion, this study shows that a high percentage of STEMI patients have inadequate levels of clopidogrel-induced and, to a lesser extent, aspirin-mediated platelet inhibition when starting a P-PCI procedure, and suggests that a poor response to clopidogrel might be associated with impaired initial TIMI flow in the IRA.
Keywords: Clopidogrel responsiveness; ST-elevation myocardial infarction; antiplatelet therapy